The potential of Fas ligand (apoptosis-inducing molecule) as an unconventional therapeutic target in type 1 diabetes - Hamad, Abdel; Arcara, Kristin; Uddin, Sophia; Donner, Thomas (Frontiers in Immunology, 2012)
The development of type1 diabetes (T1D) is driven by autoreactive T cells that attack and destroy the insulin-producing β-cells in pancreatic islets, forcing patients to take multiple daily insulin injections. Insulin therapy, however, is not a cure and diabetic patients often develop serious long-term microvascular and cardiovascular complications. Therefore, intensive efforts are being directed towards developing safe immunotherapy for the disease that does not impair host defense and preserves β-cells, leading to better glycemic control than exogenous insulin therapy. Engineering therapies that differentially cripple or tolerate autoreactive diabetogenic T cells while sparing protective T cells necessary for maintaining a competent immune system has proven challenging. Instead, recent efforts have focused on modulating or resetting the immune system through global but transient deletion of T cells or B cells using anti-CD3 or anti-CD20 mAb, respectively. However, phase III clinical trials have shown promising but modest efficacy so far with these approaches. Therefore, there is a need to identify novel biological targets that do not fit the classic properties of being involved in adaptive immune cell activation. In this prospective, we provide preclinical evidence that targeting Fas ligand (FasL) may provide a unique opportunity to prevent or cure T1D and perhaps other organ specific autoimmune diseases without causing immune suppression. Unlike conventional targets that are involved in T and B lymphocyte activation (such as CD3 and CD20, respectively), FasL is an apoptosis-inducing surface molecule that triggers cell death by binding to Fas (also known as CD95 Apo-1). Therefore, targeting FasL is not expected to cause immune suppression, the Achilles Heel of conventional approaches. We will discuss the hypothesis that targeting FasL has unique benefits that are not offered by current immunomodulatory approaches.